Role of activin, follistatin, and inhibin in the regulation of Kiss-1 gene expression in hypothalamic cell models†. Issue 2 (5th June 2019) - Tumurgan, Zolzaya; Kanasaki, Haruhiko; Tumurbaatar, Tuvshintugs; Oride, Aki; Okada, Hiroe; Hara, Tomomi; Kyo, Satoru
Abstract: Kisspeptin (encoded by the Kiss-1 gene) in the arcuate nucleus (ARC) of the hypothalamus governs the hypothalamic-pituitary-gonadal (HPG) axis by regulating pulsatile release of gonadotropin-releasing hormone (GnRH). Meanwhile, kisspeptin in the anteroventral periventricular nucleus (AVPV) region has been implicated in estradiol (E2)-induced GnRH surges. Kiss-1–expressing cell model mHypoA-55 exhibits characteristics of Kiss-1 neurons in the ARC region. On the other hand, Kiss-1 expressing mHypoA-50 cells originate from the AVPV region. In the mHypoA-55 ARC cells, activin significantly increased Kiss-1 gene expression. Follistatin alone reduced Kiss-1 expression within these cells. Interestingly, activin-induced Kiss-1 gene expression was completely abolished by follistatin. Inhibin A, but not inhibin B reduced Kiss-1 expression. Activin-increased Kiss-1 expression was also abolished by inhibin A. Pretreatment of the cells with follistatin or inhibin A significantly inhibited kisspeptin- or GnRH-induced Kiss-1 gene expression in mHypoA-55 cells. In contrast, in the mHypoA-50 AVPV cell model, activin, follistatin, and inhibin A did not modulate Kiss-1 gene expression. The subunits that compose activin and inhibin, as well as follistatin were expressed in both mHypoA-55 and mHypoA-50 cells. Expression of inhibin βA and βB subunits and follistatin was much higher in mHypoA-55 ARC cells. Furthermore, we found that expression of the inhibin α subunit and follistatin genes was modulated in the presence of E2 in mHypoA-55 ARC cells. The results of this study suggest that activin, follistatin, and inhibin A within the ARC region participate in the regulation of the HPG axis under the influence of E2. Abstract : Activin, follistatin and inhibin directly regulate the expression of Kiss-1 gene in hypothalamic Kiss-1 expressing cell models.